Peningkatan Penjualan Produk Brem Bali Dewi Sri pada PT Hatten Bali berdasarkan Strategi Segmenting Targeting dan Positioning di Bali - LESTARI, PUTU WIDHIANTI; ANTARA, MADE; YUDHARI, DEWA AYU SRI (Jurnal Agribisnis dan Agrowisata (Journal of Agribusiness and Agritourism); Vol.6, No.3, Juli 2017DO - 10.24843/JAA.2017.v06.i03.p04, 2017)
Increased sales of Dewi Sri (a brand of Balinese Rice Wine Product) at PT Hatten Bali based on Segmenting Targeting and Positioning Strategies in Bali The era of globalization results in increased business competition thus causing fluctuations in sales of products of Balinese rice wine of Dewi Sri that already experienced by PT Hatten Bali. The strategies that should be reinforced in the face of intense competition, the company should apply the strategies of segmenting, targeting and positioning. The study aimed to identify and categorize groups of buyers based on their characteristics, to select one segment of the potential market to enter, and to establish and to communicate the main benefits that differentiate the company's products with other products in the market. The research applies quantitative descriptive method by approaches of cluster analysis, crosstab, Multi Dimensional Scaling, and Correspondence Analysis which used primary data of 135 respondents. The research showed that the potential segment as target market of Balinese rice wine products of Dewi Sri which will be produced by PT Hatten Bali was the segment 1 by the segment percentage size of 63,0% compared to segment 2 (14,8%) and segment 3 (22,2%). Balinese rice wine product positioning has the advantage on product diversification and promotion attributes that differentiate it from its competitors (Eagle, Gwan Gwan Hoo, and Rice Bird) based on consumer perceptions. Therefore, PT Hatten Bali needs to create a unique product feature that is expected to increase sales of Balinese rice wine products of Dewi Sri.